Estetika Visual Pencahayaan dan Palet Warna dalam Membangun Atmosfer Sinematik Red Dead Redemption 2 - Lutfi Fauzan; Moh. Yudik Al Faruq (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Cinematic quality is a phrase that follows Red Dead Redemption 2 almost everywhere, yet the visual machinery behind that impression is rarely taken apart. This study probes the part played by lighting and color palettes in shaping the cinematic atmosphere of Rockstar Games' open-world title. The approach is qualitative and descriptive-analytical: three regions with sharply opposed moods, namely The Heartlands, Bayou Nwa, and Colter, were explored firsthand across different in-game hours and weather, then recorded as screenshots. The reading attends to light strength and direction, color temperature, contrast, saturation, and dominant hue, interpreted through color psychology and cinematographic lighting craft. Each region, it turns out, rests its mood on a different light-and-color configuration. Golden-hour warmth leaves The Heartlands open and nostalgic; washed-out greens, fog, and flattened contrast make Bayou Nwa oppressive and menacing; a near-monochrome palette under cold light renders Colter a portrait of isolation and survival. These configurations act less as ornament than as instruments of environmental storytelling, steering how players feel about the spaces they move through.